Nitrogen fertilization overweighs intercropping in promotion of dissolved organic carbon concentration and complexity in potato-cropped soil - Wang, Ding; Zhao, Ping; Xiang, Rui; He, Shuran; Zhou, Yanli; Yin, Xinhua; Long, Guangqiang (Plant and soil, 2021)
Aims Intercropping promoted land productivity and be performed worldwide. This study aimed to assess the effect of intercropping on soil dissolved organic carbon (DOC) and its nitrogen (N) regulation. Methods The potato was monocropped and intercropped with maize under four N levels (0, 62.5, 125 and 187.5 kg ha −1 for N0, N1, N2 and N3, respectively) in a fixed plot experiment from 2014 in subtropical China. Soil DOC concentration was determined and seasonal and interannual dynamics were analyzed from 2016 to 2018; Absorption values of specified wavelength were selected to characterize the annul DOC composition. Finally, the driving factors of DOC variation were explored using structural equation modeling (SEM). Results Soil DOC concentration and accumulation under N-applied treatments were higher than N0 and the increase peaked at N1. Compared with monocropping, intercropping significantly increased DOC accumulation by 20.29% only at N0. N application significantly improved the contents of amines and aromatic compounds and the average molecular weight of DOC, thus improving the degree of humification and aromatization of soil DOC. The SEM showed that the chemical composition of DOC was complicated with increasing soil temperature, aboveground and root biomass, while DOC concentration and chemical composition significantly affected the accumulation of DOC. Conclusions Agricultural diversified cropping affects the dynamics and composition of soil DOC, which is intensively regulated by N fertilization. This study expands the insight into the variable DOC concentration and composition and its role in soil organic carbon turnover under the varying fertilization and cropping patterns.